URGENCY OF STRENGTHENING INDONESIA BORDER AREA MANAGEMENT - Muhammad Rafi Darajati; Muhammad Syafei (PRANATA HUKUM, 2022)
The presence of Law Number 43 of 2008 concerning State Territory (State Territory Law) shows the seriousness of the Indonesian Government in managing border areas. Even so, there are still many problemsin border area management that need solutions to be found. This is related to the issue of the authority to manage border areas and the institution for controlling national borders as regulated in State Territory Law. This article aims to analyze the reasons for the need to strengthen border area management. The research method in this article is a normative juridical approach presented in analytical descriptive. This article concludesthat State Territory Law has not been optimally implemented to encourage the realization of the border area as Indonesia's front porch. Therefore, the revision of State Territory Law is urgent to be carried out, especially related to the management of border areas where this needs to become a separate law, unlike currently which is only a subpart of State Territory Law. Meanwhile, related to institutions, the National Agency for Border Management needs to be strengthened in its authority in managing border areas, not only for cross-agency coordination but also to be able to carry out executions. This strengthening can even reach the stage of increasing the institutionalstatusin managing border areas, namely to the Ministry stage.